Improved synthesis, characterization and catalytic application of [H(OEt2)2][BC6H3(m-CF 3)2 - Hijazi, Ahmed K.; Taha, Ziyad A.; Ajlouni, Abdulaziz; Radhakrishnan, Narayanan; Voit, Brigitte; Kuehn, Fritz E. (Journal of Organometallic Chemistry)
[H(OEt2)2][BC6H3(m-CF 3)24] has been straightforwardly prepared through a one pot reaction. The product has been characterized by elemental and thermogravimetric analysis, 1H, 13C NMR and IR spectroscopy. The catalytic activity of the acid in the polymerization of isobutene has been studied. Polymerizations were performed at a temperature interval from 0 to 30 °C. The catalytic results show conversions between 34 and 88% and between 84 and 92% in about 30 min for complexes [H(OEt 2)2][BC6H3(m-CF3) 24] and [H(OEt2)2][B(C 6F5)4], respectively. © 2014 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Catalysis; Isobutene; Oxonium acid; Polymerization